Violence Behind Bars: Analysing Human Rights Issues in Custodial Settings - Awasthi, Abhishek; Siddiqui, Seema (Journal of Neonatal Surgery, 2025)
“Jails and prisons are designed to break human beings, to convert the population into specimens in a zoo - obedient to our keepers, but dangerous to each other.”1 -Angela Davis Custodial violence is becoming one of the most serious human rights violations in India. Today, such aggression against the body affects not just criminals, but also economically, socially, and educationally disadvantaged members of society. Unfortunately, this has become commonplace and is now part of the routine. These actions only produce temporary discomfort in the minds of the public, forcing the government to deal with a widespread public outcry. In general, human rights are those that are fundamental to who we are as people and without which we cannot exist. One of the biggest democracies in the world, India, has always respected human rights. The Indian government’s commitment to upholding human rights both domestically and internationally is demonstrated by the inclusion of the concept of these rights in the Constitution and its subsequent recognition of them through its ratification of the International Covenant on Economic, Social, and Cultural Rights. Whether in South Africa, Palestine, or elsewhere, the Indian government has always taken the lead in advocating for human rights whenever they are violated. The present study is an attempt to answer the research question that whether custodial violence in India is an unavoidable consequence of the and the protections provided by international and national instruments, and, lastly, to evaluate the judiciary’s function in respect to protection of human rights in custodial violence.